2022
DOI: 10.1007/s10531-022-02367-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying an online wildlife trade using a web crawler

Abstract: Legally protected plants are illegally traded through online sales platforms and orchids are a significant component of this wildlife trade. This study focused on salep, a compound product made from wild collected orchid tubers from several genera—including Anacamptis, Dactylorhiza, Himantoglossum, Ophrys, Orchis, Serapias—whose harvest endangers some of the species used, despite their collection and sale being restricted by national and international legislation. Using a custom designed web crawler in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…As highlighted in Table 1 , this traditional preparation is still very popular in Turkey, Greece, the Balkans, and in neighbouring Iran as well, increasing the risk of extinction for several species [ 24 , 25 , 26 , 27 , 139 , 165 ]. Indeed, it has been reported that thousands of individuals are harvested every year [ 81 , 165 , 268 ]. The practice is now forbidden in many Mediterranean countries and the product is proposed mainly with guar-gum ( Cyamopsis tetragonoloba (L.) Taub.)…”
Section: Conservation Concerns and Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted in Table 1 , this traditional preparation is still very popular in Turkey, Greece, the Balkans, and in neighbouring Iran as well, increasing the risk of extinction for several species [ 24 , 25 , 26 , 27 , 139 , 165 ]. Indeed, it has been reported that thousands of individuals are harvested every year [ 81 , 165 , 268 ]. The practice is now forbidden in many Mediterranean countries and the product is proposed mainly with guar-gum ( Cyamopsis tetragonoloba (L.) Taub.)…”
Section: Conservation Concerns and Actionmentioning
confidence: 99%
“…Ghorbani et al [ 163 , 164 ] listed non-disruptive collection as a compromise to meet Salep request, with the possibility of introducing local bans in the case of substantial population decline. However, levels of sustainable harvesting are still under scientific debate, especially because there is, in general, an increasing demand of Salep made by the rising middle-class among developing countries, with a major request of exportation to Western nations (with Germany leading) that has been linked to illegal collection [ 27 , 81 , 163 , 164 , 269 ]. Kreziou et al [ 24 ] noticed that there had been a change in the utilization of Dactylorhiza species from previous reports, and they hypothesized that this was caused by the increased rarity of the more desired Anacamptis and Ophrys following overharvesting.…”
Section: Conservation Concerns and Actionmentioning
confidence: 99%
“…Its high consumption in the eastern Mediterranean area is causing serious risks to both consumers and orchids [ 5 ]. Thus, tubers are often illegally harvested causing conservation concerns [ 6 ], while the final product may be adulterated with potential health risks [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this preparation originated from the Eastern Mediterranean and the Balkans, it became famous across Europe during the Renaissance period following the trend after the publication of Gerard's Herbal in 1633 [7]. To date, it has been reported that thousands of orchid bulbs are widely harvested every year for salep in different regions [19][20][21]. In the past, orchid tubers were commonly collected in northern Greece for the preparation of salep beverages and gelatin for porridge, representing a working-class staple [22]; however, overharvesting still occurs.…”
Section: Introductionmentioning
confidence: 99%